FishPaCT: An Investment Policy Model of Fisheries Sector in the Pacific Coral Triangle Countries - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
To alleviate the detrimental impacts of changing climate and degrading ecosystems on the fisheries sector that harm the food security and livelihood opportunities of the coastal communities in the Pacific Region, the Environment and Production Technology Division of IFPRI implemented an economic analysis study on “Future Prospects and Adaptation Strategies for the Fisheries Sector under Climate Change in the Pacific Coral Triangle Countries” in 2011‐2013.